Water scarcity, gender, and Mapuche culture. An Analysis from Feminist Political Ecology (Polis (Santiago), 2019)
This article analyzes the impacts that water scarcity has had on the daily water use practices of Mapuche women in the Commune of San Juan de La Costa, Chile. It is approached from the feminist political ecology, to analyze the hydric inequalities that are experienced at domestic level in function of the gender role and the culture of water users. A mixed methodology is used, through the application of surveys, interviews and focus groups.As a result, the impacts that water scarcity generates on Mapuche women are particular, affecting their economy, emotionality and spirituality in different ways depending on the type and source of access they have. We conclude that the domestic impacts of water scarcity are heterogeneous, so it is relevant to analyze the microscale effects produced by socio-environmental inequalities.
Keywords: Drought; political ecology; gender geography; mapuche women.